Large bearing number stability analysis for Tango class gas bearing sliders - Witelski, T; Hendriks, F (1999)
Air bearing sliders in the Tango class use load bearing pads with inlet-throttled lending edges to control the mass flux and lift. The influence of leakage or diffusion effects is always present in real sliders. In some designs such as railed taper flat designs leakage is dominant. The behavior of such sliders must be determined with numerical methods that obscure deeper understanding. Many aspects of the behavior of Tango class sliders can be understood with the vast simplification allowed by inlet throttling. In this paper such a simplified analysis is applied to describe a complete air bearing slider composed of two pads. The conditions for static level Fight are determined as well as the linear stability of heaving and pitching oscillations. Both stable and unstable modes are identified Either damping or amplification can result from convective effects in the absence of mechanical damping. In real implementations of Tango class sliders instability has not been observed thanks to diffusion. The present analysis can serve as a guide to select initial choices for the operating parameters that correspond to maximum corrective damping.